Management Developing Competence of the Arabic Teachers in Pesantren Mawaridussalam Deli Serdang, North Sumatra: Ø¥Ø¯Ø§Ø±Ø© ØªÙ†Ù…ÙŠØ© ÙƒÙØ§Ø¡Ø© Ù…Ø¯Ø±Ø³ Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙÙŠ Ù…Ø¹Ù‡Ø¯ Ù…ÙˆØ§Ø±Ø¯ Ø§Ù„Ø³Ù„Ø§Ù… Ø¯ÙŠÙ„ÙŠ Ø³Ø±Ø¯Ø§Ù†Ø¬ Ø³ÙˆÙ…Ø·Ø±Ø© Ø§Ù„Ø´Ù…Ø§Ù„ÙŠØ© - Nasution, Ali Fuddin; Supriyansyah Lumbu; Nasution, Lukman Hakim (STUDI ARAB, 2023)
This research aims to describe and analyze the management of arabic teacher competencies and the influence factors in a process according to natural circumstances in Pesantren Mawaridussalam. Management of teacher competencies needs considered in order to realize the improvement of the good quality teachers. Because the role of teachers is very vital as the main actor driving in realizing good and quality learning education. This research is compiled in a descriptive qualitative approach, data collection through interviews and documentation, the analysis data technique using data reducting, presenting data and drawing conclusions. The results of this study indicate in managing teacher competence, several stages are carried out, such as recruiting teachers from recommended agencies only. The new teachers have to attend training with the leadership and Nazir Waqf for one month. Forming a formatur for educational management every year, conducting learning evaluations and making I'dat congregations every week are reflected in the form of competence of Arabic language teachers. The supporting factors are leadership and organizational factors students of language. Meanwhile, the inhibiting factors are teachers who have not been able to make and master teaching materials properly and weak commitment organizations about programs. This research finds the influence developing factors of managing the Arabic language teacher's competence.